2013
DOI: 10.1021/ic400361s
|View full text |Cite
|
Sign up to set email alerts
|

Lewis-Acid-Promoted Stoichiometric and Catalytic Oxidations by Manganese Complexes Having Cross-Bridged Cyclam Ligand: A Comprehensive Study

Abstract: Redox-inactive metal ions have been recognized to be able to participate in redox metal-ion-mediated biological and chemical oxidative events; however, their roles are still elusive. This work presents how the redox-inactive metal ions affect the oxidative reactivity of a well-investigated manganese(II) with its corresponding manganese(IV) complexes having cross-bridged cyclam ligand. In dry acetone, the presence of these metal ions can greatly accelerate stoichiometric oxidations of triphenylphosphine and sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 112 publications
4
46
0
Order By: Relevance
“…Ethylene cross-bridged tetraazamacrocycles were introduced to coordination chemists in 1990 by Weisman and Wong (Weisman et al, 1990). Since then, their transition metal complexes have become important to the fields of oxidation catalysis (Yin et al, 2007;Dong et al, 2013), medical/biological imaging (Boswell et al, 2004;Sprague et al, 2007;Silversides et al, 2011) and chemokine receptor antagonism (Lewis et al, 2005;Valks et al, 2006;Smith et al, 2012) due to the combination of restricted macrocycle configuration and kinetic inertness inherent to these ligands.Chromium(III) complexes have played an important role in characterizing new ligands due to their relative kinetic inertness (Cotton & Wilkinson, 1988). Yet, to date, only one report of the chromium coordination chemistry of these macrobicyclic ligands has appeared in the literature (Maples et al, 2009).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Ethylene cross-bridged tetraazamacrocycles were introduced to coordination chemists in 1990 by Weisman and Wong (Weisman et al, 1990). Since then, their transition metal complexes have become important to the fields of oxidation catalysis (Yin et al, 2007;Dong et al, 2013), medical/biological imaging (Boswell et al, 2004;Sprague et al, 2007;Silversides et al, 2011) and chemokine receptor antagonism (Lewis et al, 2005;Valks et al, 2006;Smith et al, 2012) due to the combination of restricted macrocycle configuration and kinetic inertness inherent to these ligands.Chromium(III) complexes have played an important role in characterizing new ligands due to their relative kinetic inertness (Cotton & Wilkinson, 1988). Yet, to date, only one report of the chromium coordination chemistry of these macrobicyclic ligands has appeared in the literature (Maples et al, 2009).…”
Section: Chemical Contextmentioning
confidence: 99%
“…26 Significant rate enhancements were generated by addition of LAs to MnO 4 − in the oxidation of alcohol 27 and alkane 28 substrates. Yin and coworkers 29 have also reported on stoichiometric and catalytic rate enhancements for OAT produced by addition of Lewis acids to manganese cross-bridged cyclam complexes. Fukuzumi, Nam, and coworkers 30 found that there is a 2,200-fold rate increase in OAT for [Mn IV (O)(N4Py)] 2+ to sulfide substrates upon binding of Sc III ions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the shifts of νas Mo = O occurred from 965 cm −1 of HPMo to 942 cm −1 corresponding to Ag 1 PMo, Ag 2 PMo, and Ag 3 PMo, respectively. This was proposed to be the interaction between Ag and terminal oxygen of Mo = O leading to some blue shifts of the IR band of νas Mo = O, which was the main contribution to acceleration of electron transferring in oxidation 37 . Such blue shifts were correlative to the amount of Ag with the order of Ag 3 PMo (23 cm −1 ) >Ag 2 PMo (21 cm −1 ) >Ag 1 PMo (15 cm −1 ).…”
Section: Resultsmentioning
confidence: 99%